Nonlinear programming for optimization sectional area in building a house / Norhafiza Khairi, Nurfarah Anis Mat Wero and Wan Nur Malihah Mat Din - Khairi, Norhafiza; Mat Wero, Nurfarah Anis; Mat Din, Wan Nur Malihah (2019)
In mathematics, nonlinear programming is the process of solving optimization problems where some of the constraints or the objective function are nonlinear. So, this research presents a nonlinear programming technique in minimizing the cost based on the area of each segment in a house. The aim of this research is to minimize the cost of house construction based on bungalow design in Malaysia by using nonlinear programming and to maximize the area of each segment of the bungalow based on the cost projected. The method used in the previous study is more focused on resizing the bedroom into same size and area but the method in this research are more focused on maximizing different size of bedrooms. The minimum cost of building the house is RM94489.82 and the maximized area of the house was 1763.18/ t2 . The validation was done by sensitivity analysis by comparing the house with different number of bedrooms.